THERMAL DEGRADATION ANALYSIS OF WOOD TREATED WITH FIRERETARDANTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Fire hazard control in wooden constructions is very important. For this purpose, fire retardants are used, which change the thermodestruction of wood and reduce combustion. The aim of the present research project was to study and compare the fire–protective properties of fire-retardants and to explain the chemical process of pyrolysis, namely, degradation in treated and untreated wood. The influence of fire-retardants on the wood thermal stability and the amount of volatile products was estimated on the basis of thermal analysis results. The volatile products (above 50%) of the pyrolysis process were identified, and the mechanism of the influence of fire-retardants on wood thermodestruction was studied.The presence of toxic compounds, formed by pyrolysis, was evaluated. The results of the study have shown that analytical pyrolysis is a modern, precise method for identifying the toxic compounds of volatile products in processes of both wood pyrolysis and combustion. The application of analytical pyrolysis enables a prompt determination of the fire protection degree of building wood constructions.